2016
DOI: 10.1159/000452489
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomalabsorption of Levothyroxine: A Challenge for the Endocrinologist in the Treatment of Hypothyroidism

Abstract: Background: Hypothyroidism due to non-compliance with levothyroxine therapy (pseudomalabsorption) is rare. The diagnosis is considered in patients with persistent severe hypothyroidism despite treatment with large doses of levothyroxine. Intestinal malabsorption, drug and dietary interference with levothyroxine absorption and nephrotic syndrome should be excluded. The diagnosis of pseudomalabsorption can be demonstrated by using “an oral 1,000 µg of levothyroxine test” showing a rapid decrease in thyroid-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 27 publications
0
30
1
Order By: Relevance
“…Earlier studies considered 2-hour rapid levothyroxine testing as a marker for normal absorption [4, 6, 17]. In the current study we found that the response to OWT treatment could not be predicted based on the T4 or fT4 rise by >50% 2 hours after administration of the first dose of OWT.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Earlier studies considered 2-hour rapid levothyroxine testing as a marker for normal absorption [4, 6, 17]. In the current study we found that the response to OWT treatment could not be predicted based on the T4 or fT4 rise by >50% 2 hours after administration of the first dose of OWT.…”
Section: Discussioncontrasting
confidence: 67%
“…In this study, a weight-related dose was used in each case, in contrast to many earlier studies where fixed doses were used [2, 3, 9]. Previous studies report that serum levels of levothyroxine are at or near their peak 2 hours after administration of an oral dose [36, 9–14]. This study showed that although the total T4 levels peak at 2 hours, the fT4 level is at maximum 24 hours after thyroxine ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Initially the clinician might suspect a decreased T4 gastrointestinal absorption (24), and an evaluation for diseases causing malabsorption, or drug interaction should be performed. Some authors suggest that an oral T4 absorption test (by giving a total amount of 600 to 2,000µg of thyroxine ) could be used to demonstrate pseudomalabsorption (4,25,26). The tablet formulations of levothyroxine contains a stable salt, sodium T4, together with a variety of excipients (27).…”
Section: How Oral Thyroxine Is Ingestedmentioning
confidence: 99%
“…The daily use of oral LT4 is the most frequent treatment of hypothyroidism and is one of the most effective, inexpensive and safe hormone replacements in endocrinology. Although in some patients hypothyroidism persists despite therapy with high doses of levothyroxine 4 . In patients with persistently elevated TSH levels, there are a number of causes, which needs to be considered, including poor administration and pathological malabsorption conditions.…”
Section: Discussionmentioning
confidence: 99%